Critique Paper: Why e-government projects fail? An analysis of the Healthcare.gov website Revisited - Nanang Husin (Jurnal Esensi Infokom : Jurnal Esensi Sistem Informasi dan Sistem Komputer, 2018)
e-government project failure has been widely discussed in the literature. Many analysis has been done that study the factor and reason, which cover cases in general or specific event. This paper is one of the literature that analysis e-government project failure too which studied on Healthcare.gov case. The paper studied on the cased based literature review analysis combined with data examination of media sources and social media. It has two research question that it try to solve with classification and metadata analysis. By using those combination data, the paper build the model and thus making analysis and conslusion. But the paper did not cleary explain how the model was built, so the result of first research question is questionable. And also the paper did not give strong foundation about the conclusion of the second research question, hence the outcome of the second research question is not clear. Should this paper adhere to this problem, this paper will give a a clear and better result.